Pengembangan Bahan Ajar Multimedia Berbasis Flipbook Materi Teknik Dasar Volley Forehand dan Backhand pada Mata Kuliah TP. Pembelajaran Tenis Lapangan - Farhan Andrian; I Gede Suwiwa; Peby Gunarto (JURNAL RISET RUMPUN ILMU PENDIDIKAN, 2026)
This study aims to develop flipbook-based multimedia instructional materials for the basic techniques of forehand and backhand volley in the Tennis Learning course. This research employed a Research and Development (R&D) approach using the ADDIE model, which consists of five stages: analysis, design, development, implementation, and evaluation. The validation subjects included a content expert, a learning media expert, an instructional design expert, and a field practitioner. Product trials were conducted with students of the Physical Education, Health, and Recreation Study Program, Faculty of Sports and Health, Universitas Pendidikan Ganesha, through individual trials involving three students, small-group trials involving seven students, and large-group trials involving twenty-one students. Data were collected using questionnaires with rating scales and were analyzed using descriptive qualitative and quantitative analysis in the form of percentages. The results indicated that the content expert validation achieved 98%, the media expert 93%, the instructional design expert 97%, and the field practitioner 98%, all categorized as very good. The individual trial obtained 97%, the small-group trial 98%, and the large-group trial 96%, all classified as very good. Therefore, the flipbook-based multimedia instructional materials on basic volley techniques are considered highly feasible for use as learning resources in tennis instruction.